Revisiting curriculum and instructions in the 21st century teaching and learning - Syed Hassan, Sharifah Sariah; Mohin, Mohaida (2019)
This product revisits four dimensions of learning domains and 21st century skills .It delivers awareness on the extension of parental partnership with teachers and communities. Examples of education system from Korea, China, Finland and Japan are discussed. Teacher Professional development is addressed with a recommendation for future training model in teacher training. Purposes 1.Highlight the issues of subject matter, pedagogy and values in Malaysia 2. Learn from education best practices in few developed countries 3. Develop a model for teacher training and professional development Methodology 1.Internet resources 2.Secondary survey data